Evaluation of efficacy of prion reduction filters using blood from an endogenously infected 263K scrapie hamster model. Issue 10 (30th May 2015) - McLeod, Neil P.; Nugent, Philip; Dixon, Douglas; Dennis, Mike; Cornwall, Mark; Mallinson, Gary; Watkins, Nicholas; Thomas, Stephen; Sutton, J. Mark
<x xml:space="preserve">Abstract</x> BACKGROUND The P‐Capt prion reduction filter (MacoPharma) removes prion infectivity in model systems. This independent evaluation assesses prion removal from endogenously infected animal blood, using CE‐marked P‐Capt filters, and replicates the proposed use of the filter within the UK Blood Services. STUDY DESIGN AND METHODS Two units of blood, generated from 263K scrapie–infected hamsters, were processed using leukoreduction filters (LXT‐quadruple, MacoPharma). Approximately 100 mL of the removed plasma was added back to the red blood cells (RBCs) and the blood was filtered through a P‐Capt filter. Samples of unfiltered whole blood, the prion filter input (RBCs plus plasma and SAGM [RBCPS]), and prion‐filtered leukoreduced blood (PFB) were injected intracranially into hamsters. Clinical symptoms were monitored for 500 ± 1 day, and brains were assessed for spongiosis and prion protein deposit. RESULTS In Filtration Run 1, none of the 50 challenged animals were diagnosed with scrapie after inoculation with the RBCPS fraction, while two of 190 hamsters injected with PFB were infected. In Filtration Run 2, one of 49 animals injected with RBCPS and two of 193 hamsters injected with PFB were infected. Run 1 reduced the infectious dose (ID) by 1.467 log (>1.187 log and <0.280 log for leukoreduction and prion filtration, respectively). Run 2 reduced prion infectivity by 1.424 log (1.127 and 0.297 log, respectively). Residual infectivity was estimated at 0.212 ± 0.149 IDs/mL (Run 1) and 0.208 ± 0.147 IDs/mL (Run 2). CONCLUSION Leukoreduction removed the majority of infectivity from 263K scrapie hamster blood. The P‐Capt filter removed a proportion of the remaining infectivity, but residual infectivity was observed in two independent processes.